Biologically active substances of milk-protein concentrates with berry puree - Deinychenko, Liudmyla (My University, 2017)
This work provides the results of studies of organic acids and P-vitamin substances content in cranberry and viburnum puree, used as coagulants, and in MPC obtained with their use.
Keywords: сколотини; калина; молочно-білкові копреципітати; антиоксиданти; пахта; buttermilk; viburnum; milk-protein co-precipitates; antioxidants; кафедра технології ресторанної і аюрведичної продукції